Antecedents and Effects of Substance Abuse and Addiction among Urban Adolescents in Kenya - Wawasi, Kamau Damaris; Nderu, Kiragu (Journal of Advanced Psychology, 2017)
Purpose: The study sought to determine antecedents and effects of substance abuse and addiction among urban adolescents in Kenya Methodology: The study was a survey research that incorporated quantitative form of research. It involved self-administration of a questionnaire that integrated structured or closed-ended questions. This study was conducted at Nairobi Pentecostal Church-Karen, Kenya. A total of one hundred respondents (fifty boys and fifty girls) were picked through simple random sampling. The questions were answered on the spot and handed over to the researcher. Resuts: Results revealed that various factors lead the adolescents to the use of DSA. These factors include peer pressure, family problems, adjusting to studies and negative media.Results revealed that there are various causes of DSA addiction. This includes peer pressure and family environment. Results revealed that there is a strong relationship between DSA and STDs, HIV and unwanted pregnancy. Finally, the study concludes that adolescent male is more prone to DSA than adolescent female. Unique contribution to theory, practice and policy: It was recommended that youths be engaged in youth programmes so that they may spread word of drug abuse to other fellow youths. The study also recommended that parents and guardians to emphasize discussions with their children on drug issues so as to make them aware and know the effects of drug abuse. It is also recommended that all schools to educate youths on use of drug abuse, effects and the consequences of drug abuse. The study recommends that family based programs to reach families of children at each stage of development to be implemented and to train parents in behavior skills.